HUBUNGAN PELAYANAN KEPERAWATAN RUANG RAWAT INAP DENGAN TINGKAT KEPUASAN PASIEN BPJS DI PUSKESMAS SEMBORO KECAMATAN SEMBORO KABUPATEN JEMBER - Emi Eliya Astutik; Eka Fitriya (Jurnal Kesehatan dr. Soebandi, 2017)
Nursing Services is one of the professional services that includes overall services (biological, psychological, social, and spiritual) and is aimed at individuals, families, and the sick and healthy community. Nursing services are very important for patients at the Puskesmas. The good nursing services at the health center can be seen from the satisfaction of the patient himself. The purpose of this study was to determine the relationship between inpatient nursing care and BPJS patient satisfaction at the Semboro Health Center. The study design uses analytic survey with cross sectional approach. The population of respondents was 44 respondents. The sampling technique used was acidental sampling by taking patients who were available at the time of the study at Semboro Health Center, which numbered 44 patients. The study was conducted in the inpatient room by using a questionnaire for data collection, so the data obtained were primary data. The results showed that as many as 13.6% of respondents rated nursing services in the good category and 86.4% of respondents rated not good. The level of satisfaction of 22.7% of respondents is at the level of satisfaction and 77.3% of respondents is at the level of satisfaction is not satisfied. Statistical test calculations with Chi Square obtained Pvalue = 0,000 With a correlation coefficient of 0.591 means that the correlation is sufficient. Ha is accepted (p value α α 0.05), so it can be concluded that there is a significant relationship between inpatient nursing services with the level of BPJS patient satisfaction at the Semboro Health Center in Jember Regency